2020
DOI: 10.1155/2020/7124394
|View full text |Cite
|
Sign up to set email alerts
|

Can Superabsorbent Polymers Improve Plants Production in Arid Regions?

Abstract: Superabsorbent polymers (SAPs) have shown to be quite effective and useful in acting as a reservoir for water and some nutrients in arid and semiarid regions. There are many studies in Iran that have been performed in relation to SAPs and their useful application in agriculture; however, there is still a lack of its applied definition in arid regions. Therefore, this study was conducted with the aim of doing a meta-analysis of the results of studies conducted in Iran and answering a general question about whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Superabsorbent polymers (SAPs) are widely used as containers for water and plant nutrients, especially in arid and semiarid regions, since they significantly improve water usage efficiency [ 21 ]. According to a recent review, the application of 100 kg SAP per hectare is the most appropriate rate for increasing seed and dry matter yields and satisfying economic aspects, allowing to increase in cereal seed yield by more than 15% [ 22 ].…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 99%
“…Superabsorbent polymers (SAPs) are widely used as containers for water and plant nutrients, especially in arid and semiarid regions, since they significantly improve water usage efficiency [ 21 ]. According to a recent review, the application of 100 kg SAP per hectare is the most appropriate rate for increasing seed and dry matter yields and satisfying economic aspects, allowing to increase in cereal seed yield by more than 15% [ 22 ].…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 99%
“…Superabsorbent polymers (SAPs) or hydrogels are cross‐linked hydrophilic polymers able to absorb significant quantities of water of up to 1000 times their dry weight (Li et al ., 2014; Lejcuś et al ., 2018). By binding a large amount of water in the soil and making it available to the plants for longer periods, crop yields can be improved, especially in arid regions (Hou et al ., 2018; Satriani et al ., 2018; Jahan and Nassiri Mahallati, 2020).…”
Section: Microbial Polysaccharides: Functionalities and Their Applicability In Industrymentioning
confidence: 99%
“…It has been reported that the highest sesame (Sesamum indicum L.) SY obtained when 80 kg ha −1 SAP, 6 kg ha −1 humic acid, and 50% of the sesame water requirement during the growing season were applied (Nassiri-Mahallati and Jahan 2020). The results of the meta-analysis performed on the published studies regarding the application of SAP in crop production in Iran indicate the positive effect of SAP on biomass production and grain yield of various crops across arid regions of the country (Jahan and Nassiri-Mahallati 2020).…”
Section: Introductionmentioning
confidence: 98%